Fear of the unknown: Experience of frontline healthcare workers with coping strategies used to face the COVID 19 pandemic. - Gabriela Arango-Martinez; Laura Becerra Sarmiento; Isabela Castaneda Forero; Laura Castaneda Carreno; Yazmin Cadena-Camargo (Public Library of Science (PLoS), 2024)
The COVID 19 pandemic presented various challenges among health care workers, one of them being the impact it has on mental health. The psychological problems such as anxiety, depression, insomnia and stress, all consequences of the pandemic cause psychopathological outcomes reverberating negatively on the emotional well-being of health care workers. This study aimed to explore the experience of frontline healthcare workers (HCWs) during the COVID-19 pandemic in a middle-income country in Latin America and to identify the coping mechanisms they used to face stressful situations during this time. A qualitative study based on an interpretative paradigm was conducted allowing to examine complex, ambiguous and emotionally loaded topics to explore in detail the experience of frontline HCWs during the COVID-19 pandemic. Through convenience sampling eleven frontline HCWs were recruited to participate in semi-structured interviews. An inductive analysis was done with four pre-established categories: the experience of HCWs during the attention of COVID-19 patients, the experience during their own infection, the experience during the work reintegration and the coping mechanisms used. Our results show that fear and uncertainty predominated throughout the attention of COVID-19 patients. Participants used both coping strategies based on problem-solving efforts, such as routine changes, and emotional management efforts, like social support or psychological counselling. The choice of coping strategies was influenced by their personal beliefs, past emotional experiences, and prior medical formation. These findings provide public and private institutions insight for creating effective policies, based on the HCWs' preferences, to promote their psychological well-being.